RANCANGAN INSTRUMEN KEAKURATAN KODE DIAGNOSIS KASUS KANKER RAWAT JALAN BERDASARKAN ICD-10 TAHUN 2022 - Rahmawati, Fitria Dewi (Jurnal Informasi Kesehatan Indonesia (JIKI), 2025)
HK.02.02/MENKES/410/2016 concerning Hospital Implementing Cancer Registration and Hospital Center for Controlling National Cancer Burden Data. The regulation states that one of the stages of hospital-based cancer registration is coding. The coding in question is the activity of assigning clinical classification codes in accordance with the international classification of diseases and medical procedures. The precision or accuracy of a diagnosis code can affect form completion, electronic transactions, and the identification of specific diagnoses and clinical procedures related to the claim. One solution to make it easier to review codes is to confirm the completeness of medical information and the accuracy of ICD 10 coding with a clinical audit instrument. The aim of this research is to design a clinical audit instrument as a tool to measure the accuracy of ICD 10 codefication diagnoses. The method used is research and development with research stages namely Analysis, Design, Development, Implementation, Evaluation. Observations are made on the Electronic Medical Record display. The data collection method used is document review. The result of the research is the Cancer Qualitative Audit Application (APDITLITKA) to facilitate audits in cancer cases. It is hoped that the development of this clinical audit information system can produce better data accuracy.